Revitalisasi Nilai Lokal Melalui Pendidikan di Era Teknologi - Thaib, Jamaluddin (Jurnal Ilmiah Guru Madrasah, 2024)
The digital era has brought about major transformations in the world of education, both in terms of teaching methods and the content delivered. However, behind this progress lies a serious challenge in preserving and transmitting local wisdom values to the younger generation. This study aims to explore how education can serve as a strategic tool in revitalising local values to ensure they remain relevant and vibrant amidst the currents of globalisation and digitalisation. Through a qualitative approach and literature review, the author outlines the importance of integrating local values into the curriculum, the use of digital media based on local culture, and the role of educators as agents of cultural identity preservation.